A Synergy between Pharmacy and Biotechnology in the Development of Precision Therapies to Enhance the Quality of Healthcare Services - Rifa Andriana; Aiman Fariq; Nina Anis (Journal of Advanced Pharmaceutical Research Sciences and Sustainability (JAPRSS), 2026)
Background. The increasing heterogeneity of patient responses to pharmacotherapy has driven a paradigm shift from conventional treatment approaches toward precision medicine. This shift requires strong integration between pharmaceutical sciences and biotechnology to ensure targeted, safe, and effective therapy. Purpose. This study aims to analyze the role of synergy between pharmacy and biotechnology in the development of precision therapy and its contribution to improving the quality of healthcare services. Method. This research employed a qualitative literature review method by analyzing scientific articles, review papers, and policy reports published between 2015 and 2025. Data were collected from reputable international databases and analyzed using a descriptive-analytical approach. Results. The findings indicate that biotechnological innovations such as pharmacogenomics, monoclonal antibodies, and molecular diagnostics significantly support pharmacists in optimizing individualized therapy. The integration of these technologies enhances therapeutic effectiveness, minimizes adverse drug reactions, and improves patient safety. Conclusion. The synergy between pharmacy and biotechnology constitutes a fundamental pillar in the advancement of precision therapy and plays a strategic role in strengthening patient-centered and sustainable healthcare services.